Improving template-based CT data evaluation by integrating CMM reference data into a CAD model-based high fidelity triangle mesh. Issue 5 (3rd September 2022) - Müller, Andreas Michael; Hausotte, Tino
ABSTRACT: Industrial X-ray computed tomography is a relatively recent technology in the field of 3D coordinate metrology. The available technical solutions represent capable systems, which are continuously adapted for different applications. Nonetheless, some profound limitations and technical challenges remain (e.g. effects of the polychromatic X-ray spectrum and a strong correlation between image quality and measurement duration), which require continuous efforts in order to improve the accuracy of such systems in the context of dimensional metrology. Therefore, this contribution demonstrates the integration of CMM measurement data into a CAD model in order to generate full reference measurements, which can be used to evaluate the measurement accuracy of CT systems. Currently, much effort is being made in order to improve simulations of CT systems with the goal to realistically recreate real CT measurements. In order to validate the simulation model by comparison against physical CT measurements, the geometry of the measurement object has to be known as accurately as possible. The presented approach shows how to generate geometries from CMM reference data which are suited to be used as an input for CT simulation tools. Detailed technical descriptions of the algorithms are given and demonstrated based on real measurements.